2012
DOI: 10.1063/1.3679604
|View full text |Cite
|
Sign up to set email alerts
|

Na incorporation into Cu(In,Ga)Se2 thin-film solar cell absorbers deposited on polyimide: Impact on the chemical and electronic surface structure

Abstract: The following article appeared in Journal of Applied Physics 111.3 (2012): 034903 and may be found at http://scitation.aip.org/content/aip/journal/jap/111/3/10.1063/1.3679604Na has deliberately been incorporated into Cu(In,Ga)Se2 (CIGSe) chalcopyrite thin-film solar cell absorbers deposited on Mo-coated polyimide flexible substrates by adding differently thick layers of NaF in-between CIGSe absorber and Mo back contact. The impact of Na on the chemical and electronic surface structure of CIGSe absorbers with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…For a NaF thickness higher than 20 nm contradictory reports appear: cell degradation; peeling off of the CIGSe layer during the chemical bath deposition of CdS; or no effects. This approach has been used in several CIGSe growth processes: the traditional three-stage [8,121], low temperature co-evaporation processes [118,119], in-line co-evaporation processes [16,122,123], rapid thermal annealing [124] and both on flat and flexible substrates like steel [125] and polyimides [126,127]. For CZTSSe the same thickness range has been reported [78,80] but no detailed studies about the effects of thick or thin layers are yet known.…”
Section: Naf As a Precursormentioning
confidence: 92%
“…For a NaF thickness higher than 20 nm contradictory reports appear: cell degradation; peeling off of the CIGSe layer during the chemical bath deposition of CdS; or no effects. This approach has been used in several CIGSe growth processes: the traditional three-stage [8,121], low temperature co-evaporation processes [118,119], in-line co-evaporation processes [16,122,123], rapid thermal annealing [124] and both on flat and flexible substrates like steel [125] and polyimides [126,127]. For CZTSSe the same thickness range has been reported [78,80] but no detailed studies about the effects of thick or thin layers are yet known.…”
Section: Naf As a Precursormentioning
confidence: 92%
“…Sodium -incorporated into the absorber by (uncontrolled) diffusion from the underlying soda lime glass substrate -is known to modify the CIGSe properties and improve the cell efficiency. [2]- [5] A controlled incorporation of alkali elements in the absorber by means of a post-deposition treatment (PDT) employing alkali-fluorides helps to further enhance performance. [6]- [8] While it was shown that a combined NaF/KF-PDT significantly enhances the device efficiency [7], its impact on the chemical, electronic, and topographical absorber structure is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Two different chemical environments of Na are observed for the CIGSe_2. The first contribution (α 1 * = 2061.2 eV) is detected for all CIGSe samples and is in same energy region as α*(Na) values of Na 2 O, Na 2 SeO 3 and Na 2 CO 3 [1]. It corresponds to Na in an oxidized environment.…”
Section: B Na Diffusionmentioning
confidence: 87%
“…Beneficial effects of alkali and especially of Na onto CIGSe based solar cell performance is well known for a long time and has been extensively discussed [1]- [4]. In fact high efficiencies are only reached when appropriate amount of Na is available prior, during or after CIGSe growth process [5]- [6].…”
Section: Introductionmentioning
confidence: 99%